Comparison of the Rheological Properties of Plant Proteins from Various Sources for Extrusion Applications - Patrick Wittek; Goeran Walther; Heike P. Karbstein; M. Azad Emin (Foods, 2021)
Plant proteins in foods are becoming increasingly popular with consumers. However, their application in extruded products remains a major challenge, as the various protein-rich raw materials (e.g., from different plant origins) exhibit very different material properties. In particular, the rheological properties of these raw materials have a distinct influence on the extrusion process and must be known in order to be able to control the process and adjust the product properties. In this study, process-relevant rheological properties of 11 plant-based protein-rich raw materials (differing in plant origin, protein content, and manufacturer) are determined and compared. The results demonstrate distinct differences in the rheological properties, even when plant origin and protein content are identical. Time sweeps reveal not only large differences in development of viscosity over time, but also in magnitude of viscosity (up to 15-fold difference). All materials exhibit gel behaviour and strain thinning behaviour in the strain sweeps, whereas their behaviour in the non-linear viscoelastic range differs greatly. Typical relaxation behaviour of viscoelastic materials could be observed in the stress relaxation tests for all materials. Comparison of the maximum achieved shear stress, which correlates with the elastic properties, reveals an up to 53-fold difference. The results of this study could serve as a starting point for adapting raw material selection and composition to process and product design requirements and help to meet the challenge of applying plant-based proteins in food extrusion.